ETIKA PENGGUNAAN MEDIA SOSIAL DI KALANGAN REMAJA - Wellyana Wellyana; Septina Lisdayanti; Loliek Kania Atmaja; Fetriani Fetriani; Syarkati Syarkati (Gapenas Publisher, 2022)
Social media is one of the technological developments that has a big role in providing convenience for humans to communicate and socialize. Beginning with the era of Friendster and MySpace, the era of Facebook and Twitter, and most recently Google Plus, this media has triggered many changes in human socialization. This is in accordance with the original purpose of why social media was created, which is to allow us to communicate and interact with other people around the world to find new friends, life partners, do business, and even do politics. So, it is important for all of us to be able to minimize the negative impacts and maximize the positive impacts of using social media